Microstructural evolution and failure mechanism of 62Sn36Pb2Ag/Cu solder joint during thermal cycling. (August 2019) - Li, Qi-hai; Li, Cai-Fu; Zhang, Wei; Chen, Wei-wei; Liu, Zhi-Quan
Abstract: To clarify the mechanism leading to solder joint failure easily in multi-field conditions in electronics system, the microstructural evolution of 62Sn36Pb2Ag/Cu solder joint during thermal cycling was investigated precisely using scanning electron microscopy and transmission electron microscopy. It was found that the as-reflowed microstructure of the solder joint was compact and uniform, being consist of Sn, Pb and Ag3 Sn phases within original solder and Cu6 Sn5 compound at the interface to Cu substrate. Addition of 2 wt% Ag resulted in isolated Ag3 Sn particles (0.2–0.5 μm in diameter) distributed in Sn matrix of the solder joint. During thermal cycling process, the microstructure of solder became more and more coarsening, especially the average diameter of Pb particles increased to more than 3.5 times larger after 2500 thermal cycles. Moreover, Cu3 Sn was generated at Cu6 Sn5 /Cu interface, and the total thickness of IMC layer increases almost linearly with the number of cycles. Due to the difference in coefficients of thermal expansion (CTE) among PCB board, Cu substrate and solder alloy, thermal mismatch occurred and contributed to the microstructural coarsening of solder alloy. Furthermore, due to the difference of expansion and contraction between Pb phase and Sn phase in the solder, cracks were formed and propagated along the interface between these two phases, which can accumulate and result in final failure of the solder joint thoroughly. Highlights: Addition of Ag results in dispersed Ag3 Sn isolated particles (0.2–0.5 μm) in Sn matrix. Microstructural coarsening takes place inside solder alloy during thermal cycling. The total thickness of IMC layer increases linearly with the number of thermal cycles. Microcracks initiate at the interface between Pb and Sn and finally lead to breakage.